Effect of passive hyperthermia on working memory resources during simple and complex cognitive tasks - Gaoua, N.; Herrera, C. P.; Periard, J. D.; El Massioui, F.; Racinais, S. (Frontiers in Psychology, 2018)
The aim of this study was to verify the hypothesis that hyperthermia represents a cognitive load limiting available resources for executing concurrent cognitive tasks. Electroencephalographic activity (EEG: alpha and theta power) was obtained in 10 hyperthermic participants in HOT (50°C, 50% RH) conditions and in a normothermic state in CON (25°C, 50% RH) conditions in counterbalanced order. In each trial, EEG was measured over the frontal lobe prior to task engagement (PRE) in each condition and during simple (One Touch Stockings of Cambridge, OTS-4) and complex (OTS-6) cognitive tasks. Core (39.5 ± 0.5 vs. 36.9 ± 0.2°C) and mean skin (39.06 ± 0.3 vs. 31.6 ± 0.6°C) temperatures were significantly higher in HOT than CON (p < 0.005). Theta power significantly increased with task demand (p = 0.017, ?2 = 0.36) and was significantly higher in HOT than CON (p = 0.041, ?2 = 0.39). The difference between HOT and CON was large (?2 = 0.40) and significant (p = 0.036) PRE, large (?2 = 0.20) but not significant (p = 0.17) during OTS-4, and disappeared during OTS-6 (p = 0.87, ?2 = 0.00). Those changes in theta power suggest that hyperthermia may act as an additional cognitive load. However, this load disappeared during OTS-6 together with an impaired performance, suggesting a potential saturation of the available resources.